First Report of Porrorchis Nickoli (Acantocephala: Plagiorhynchidae) and Cruzia Sp. (Nematoda: Kathlanidae) as parasites of Philander Opossum (Mammalian, Didelphidae) from Chiriqui, Panama - Corella, Henrry (Universidad Autónoma de Chiriquí, 2020)
A study was conducted on the internal parasitology of an individual of Philander opossum, captured in the La Verguenza creek, Chiriqui-Panama. Two intestinal parasites are recorded at first time for P. opossum (Porrorchis nickoli and Cruzia sp.) in Panama.